Equivalence of a part of derivatives of chains in the boundary value problems for the second-order ordinary differential equations - Ashurov , S. В. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A method is proposed for obtaining criteria for the equivalence of a part of derived chains of boundary-value problems for second-order differential equations with a spectral parameter in boundary conditions.